THE RELATIONSHIP BETWEEN HUMANS, SOCIETY AND CULTURE - Ratnasari; Firman; Riska Ahmad (Literasi Nusantara, 2021)
This article discusses "The Relationship Between Humans, Society and Culture". Humans, society and culture there are 3 important things that cannot be separated from their role in life. As we often hear that without the existence of society, culture cannot be preserved. The aim to be achieved in this research is to reveal the relationship between humans, society and culture itself. This research is a library research (library research). Library research is research that obtains data or materials needed from libraries in the form of books, encyclopedias, dictionaries, journals, documents, magazines and so on. The results of this study reveal that culture is the most basic element of a society, so that until now some sociologists and anthropologists still adhere to the notion of cultural determinism, namely that attitudes and patterns of human behavior in society are determined by culture.